On the F-Bernstein polynomials - Erdem, Alper; Dişkaya, Orhan; Menken, Hamza (Ukrains’kyi Matematychnyi Zhurnal, 2024)
UDC 517.5 We construct a new Bernstein operator, which is called the F-Bernstein operator obtained by using the F-factorial (Fibonacci factorial) and the Fibonomial (Fibonacci binomial). Then we examine the F-Bernstein basis polynomials and some of their properties. Moreover, we acquire certain connection between the F-Bernstein polynomials and the Fibonacci numbers.